A cystic artery arising from the middle hepatic artery detected during laparoscopic cholecystectomy: a case report. Issue 1 (13th January 2022) - Kim, Sung Hyun; Park, Sejin; Choi, Jangkyu
Abstract: We herein report a case in which a cystic artery arising from the middle hepatic artery (MHA) was encountered during cholecystectomy. A 42-year-old man visited the outpatient department complaining of chronic epigastric pain and a laparoscopic cholecystectomy was decided upon. During the preoperative evaluation, an interesting finding was observed on computed tomography. The patient had a cystic artery arising from the MHA. An MHA derived from the hilum of the proper hepatic artery runs along the medial border of the gallbladder and enters segment IV. In the operative field, the MHA that entered segment IV was observed. Dissecting downward along the MHA, a cystic artery was observed around the cystic duct. The cystic artery and duct were isolated and each was separately ligated and cut. Rare anatomical variations of the cystic artery, as in this case, can be a pitfall inducing complications during cholecystectomy.